Improved opto-electrical behavior of ZnO/C60 core/shell type organic–inorganic heterostructure. (January 2015) - Krishnaveni, M.; Devadason, Suganthi
Graphical abstract: Highlights: ZnO/C60 core/shell-type heterostructure has been successfully prepared. Deposition of a thin layer of C60 shell layer on the surface of ZnO nanorods are clearly depicted through HRTEM images. Two different absorption edges for core ZnO and shell C60 are evident from UV–visible spectra. Enhancement in NBE emission in PL spectra is explained for ZnO/C60 core/shell NRAs. Decrease in resistivity for ZnO/C60 core/shell NRAs has been demonstrated under illumination. Abstract: We report a successful synthesis of ZnO/C60 core/shell-type organic–inorganic hybrid nanorod arrays (NRAs) using simple chemical route. X-ray diffraction pattern (XRD) reveals hexagonal crystal structure of ZnO along with the face-centered cubic (fcc) structure of C60 . Detailed Fourier transform infrared spectroscopy (FTIR) inferred the attachment of C60 on the surface of ZnO NRAs. HRTEM observation confirmed ∼3 nm thickness of a very thin C60 nanocrystals shell layer formation. HRSEM image shows the existence of C60 on vertically aligned ZnO NRAs. UV–visible absorption spectra have two absorption edges corresponding to the energy band gap values of 3.05 and 1.83 eV which arise due to core ZnO and shell C60 respectively. Photoluminescence spectra reveal a strong enhancement in the NBE emission and suppression in the deep-level emission on the surface modified ZnO NRAs. The measured electrical resistivity under illumination for ZnO/C60 core/shell is lower than that of bare ZnO NRAs.